Edukasi pencegahan sindrom kelelahan (burnout) pada karyawan Pertamina MOR II Palembang - veny larasati; Bintang Arroyantri P; Ziske Maritska; Nita Parisa; Diyaz Syauki Ikhsan (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2020)
Education for Preventing Burnout Syndrome to Pertamina MOR II Palembang workers. Burnout is a syndrome that occurs due to prolonged interpersonal stress due to work. Burnout can also be described as psychological fatigue caused by work. This can occur due to the high demands of the company to provide optimal work results that the employees cannot tolerate. There are three things that can trigger this syndrome, namely excessive workload, neglect of work results and feelings of underappreciation at work. Based on a survey conducted in America, the main reason of stress was due to excessive workload, 1 in 5 employees experienced burnout syndrome which is around 46%, and in Indonesia, the survey results showed that around 64% of employees experienced increased fatigue due to work, and around 20% of employees believed that psychological fatigue is the cause of the absence of employees due to illness in the company. This community service is carried out at the request of the PERTAMINA Palembang Company. Burnout syndrome is a serious problem for employees and employers. If not addressed properly, it will lead to serious psychological problems for employees such as decreased productivity, withdrawal from work, depression and even anxiety, which in turn can have a negative impact on the company. For this reason, it is necessary to have monitoring and evaluation related to the psychological condition of employees on a regular basis.